PEMANFAATAN TEKNOLOGI RADIOGRAFI PORTABEL UNTUK MENINGKATKAN AKSES SKRINING TUBERKULOSIS DI DAERAH KEPULAUAN : EVALUASI IMPLEMENTASI DARI TERNATE - Simon Sani Kleden; febtian cendradevi nugroho; Yustinus Rindu; Dominggos Gonsalvez; Sabinus Bunga Ama Kedang; Kinanthi Lebdawicaksaputri; Maria Agustina Making; Antonia Helena Hamu; Roswita Victoria Rambu Roku (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
In archipelagic regions such as Ternate, where access to healthcare services and diagnostic facilities is limited, tuberculosis (TB) remains a public health problem with high incidence and mortality rates. The risk of TB transmission increases due to geographical conditions, shortages of healthcare personnel, and limited early detection efforts. This community service program aimed to improve early detection of tuberculosis and enhance public understanding of TB prevention and management through community-based systematic screening. The methods used included socialization, health education, screening using portable X-ray, initial examinations, assistance, and referral services for high-risk communities. The activity was conducted in Ternate from May 16 to 17, 2025, involving 112 participants. The results showed that 87 individuals had suspicious lung lesions based on portable X-ray examinations, and 56 individuals were confirmed positive for TB after further examinations. In addition, public awareness regarding TB prevention, symptoms, and transmission increased from 55% before the activity to 93% after the activity. The findings indicate that TB screening using portable X-ray technology is effective in improving early TB detection and increasing community knowledge regarding TB prevention and control.